Pengaruh Penerapan Strategi Bisnis dan Sistem Informasi Akuntansi terhadap Kinerja Usaha Mikro Kecil Menengah (UMKM) Kota Yogyakarta - Erina Kambulawa; Tri Siwi Nugrahani; Sulkhanul Umam; Tias Budi Lestari (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study aims to examine the influence of business strategies and accounting information systems on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Yogyakarta City. A total of 500 MSME owners were selected using purposive sampling based on several criteria, including having operated for more than one year, using an accounting information system to record transactions, preparing financial reports, and achieving a minimum turnover of IDR 3,000,000 per month. The results show that both business strategy implementation and the use of accounting information systems have a significant positive effect on MSME performance. Business strategies enable MSMEs to respond to market dynamics, optimize resources, and strengthen operational direction. Meanwhile, accounting information systems support accurate financial recording, analysis, and decision-making processes. Together, these two aspects improve efficiency, competitiveness, and overall business outcomes. The study suggests that MSMEs in Yogyakarta need to continue strengthening strategic planning and technology adoption to achieve sustainable performance growth.